The Impact of Parental Smoking Behavior and Cigarette Expenditure on Toddler Well-Being and Family Mental Health: A Qualitative Study Post Kabar Besti Program: A Qualitative Study - Trisnowati, Heni; Zahra, Aini; Hidayat, Muhammad Syamsu; Jatmika, Septian Emma Dwi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background. Cigarette consumption among parents has a multidimensional impact, ranging from family economic losses to declining toddler health, including an increased risk of stunting. The Kabar Besti (Smoke-Free and Stunting-Free Families) program was initiated as an innovation to control cigarette consumption and reduce stunting in children under five through a participatory approach at the community level. Objectives. This qualitative study aimed to explore changes in parental smoking patterns, cigarette expenditure shifting, and the impact on toddler health after the implementation of the Kabar Besti program in Sleman, Yogyakarta. Methods. A Rapid Assessment Procedure (RAP) design was used for this type of qualitative research. There were seven research subjects, with three key informants and four triangulation informants obtained through the purposive sampling technique. Data collection methods consisted of interviews and observations. Results. The Kabar Besti program contributes positively to changes in parental smoking behavior and shopping shifts that have an impact on improving the health of toddlers. Parents (fathers) of toddlers began to divert cigarette expenditures for nutritional needs and savings and reduce smoking habits in the house and near children. In addition, there was a decrease in the percentage of stunting among under-fives from 25% to 11.11% in two years of program implementation. These findings confirm that community-based interventions targeting parental smoking behavior are effective in improving the health of children under five and optimizing the allocation of family expenditure for children's nutritional needs